Nutritional status and living conditions of rural schoolchildren from Tucumán, Argentina: A cross-sectional observational study - Salazar Burgos, Ramiro Joaquín (2021)
Introduction: The objective was to analyze the nutritional status, social, economic and environmental conditions and lifestyles of schoolchildren residing in rural areas of Famaillá, Tucumán. Material and Methods: A cross-sectional observational study was carried out in schoolchildren between 10.0 and 15.9 years of age, of both sexes, living in rural areas of the department of Famaillá. Weight and height measurements were made and the indicators of BMI/Age and Height/Age were calculated to estimate nutritional status. The reference tables of the World Health Organization (WHO) were used. Socio-economic, environmental and lifestyle conditions were analyzed using a questionnaire that was answered by the schoolchildren. Results: In 356 schoolchildren (196 men and 163 women), 54.3% presented adequate nutritional status; 5.6% undernutrition (3.9% Short Height/Age and 1.7% Low BMI/Age) and 40.1% overweight (21.3% overweight and 18.8% obesity). The results reported that the predominant consumption was saturated fats, refined flours and sugars through bakery products, sugary drinks and sweets, followed by fruits, meats and yogurt. The 72.5% of the schoolchildren performed weekly physical exercise and 67.7% did not exceed 3 hours a day in front of television and computer screens. Conclusions: Undernutrition, particularly linear growth retardation, constitutes a current problem and coexists with accelerated increases in overweight and obesity in the rural areas of Tucumán. The epidemic condition of overweight is reaffirmed. These results show that the nutritional and epidemiological transition processes negatively impact rural areas, whose socio-economic and environmental deficiencies aggravate the public health problem, in a prospective perspective. However, there are protective factors in diet and lifestyle that could be used in the development of health strategies to improve the nutritional status of these populations.